The Cranny - Una Krizmanić Ožegović; Korana Serdarević ([sic])
“My darling sister, you have a hole in your butt,” Ivka says in all seriousness, as if relating a particularly important discovery. Children giggle and point fingers at the torn up stitching right in the middle of Tona’s round butt. Tona has just bent over while dragging the wooden stool from the kitchen, and now, broad and strong, she stands up next to the stone table. Villagers let go of their chatting and prick their ears up. There is a smile lurking at the corner of their lips – they know what their Tona is all about. Even now, when you can clearly make out her white panties under the wide, colourful skirt, it doesn’t cross her mind to cover the hole with her hand, let alone feel embarrassed. On the contrary, it’s as if she has been waiting for fancy Miss Ivka to slap that remark in the middle of a hot summer afternoon. Her tiny eyes pop with delight and people know her tongue, so sharp and witty, is half way out to snap back at Ivka.“First, it’s not a hole, it’s a cranny,” she fires. “And second, what, there’s no cranny in your fanny?!”